Hierarchical population genetic structure in the commercially exploited shrimp Crangon crangon identified by AFLP analysis - Weetman, D.; Ruggiero, A.; Mariani, S.; Shaw, P. W.; Lawler, A. R.; Hauser, L. (Marine biology, 2007)
The coastal shrimp Crangon crangon is an ecologically and commercially important species but there is limited knowledge of its genetic population structure. We utilised amplified fragment length polymorphisms (AFLPs) to investigate population differentiation among eight sampling locations comprising paired sites from north- and south-western Britain, the eastern English Channel and the Baltic Sea. Initial AMOVA and cluster analysis suggested strong differentiation, but outlier analysis identified three loci that might be subject to selection, one of which showed significant latitudinal variation in allele frequencies. Following exclusion of these outlier loci, and also of a divergent, genetically-impoverished sample from the UK Bristol Channel, cluster analysis revealed three major groupings, corresponding to geographical regions: western Britain, the eastern English Channel and the Baltic Sea. AMOVA identified significant differentiation both within and among these regions, with similar variation explained by each hierarchical level. C. crangon shows greater genetic structuring than has been found in many decapod crustaceans studied to date, and our results are consistent with unstable population sizes and gene flow restricted by distance and probably also hydrographic features. Further investigation of temporal stability in population structure is required, but broad-scale homogeneity of fishery stocks should not be assumed.